Sarcopenia as a prognostic predictor of liver cirrhosis: a multicentre study in China. Issue 6 (14th September 2021) - Zeng, Xin; Shi, Zhi‐Wen; Yu, Jia‐Jun; Wang, Li‐Fen; Luo, Yuan‐Yuan; Jin, Si‐Min; Zhang, Li‐Yuan; Tan, Wei; Shi, Pei‐Mei; Yu, Hong; Zhang, Chun‐Qing; Xie, Wei‐Fen
Abstract: Background: Diagnostic criteria for sarcopenia have not been established in Chinese. This study established criteria based on the L3‐skeletal muscle index (L3‐SMI) and assessed its value for outcomes predicting in cirrhotic Chinese patients. Methods: Totally 911 subjects who underwent a CT scan at two centres were enrolled in Cohort 1 (394 male and 417 female subjects, aged 20–80 years). The data of those subjects younger than 60 years (365 male and 296 female subjects) were used to determine the reference intervals of the L3‐SMI and its influencing factors. Cohort 2 consisted of 480 patients (286 male and 184 female patients) from three centres, and their data were used to investigate the prevalence of sarcopenia and evaluate the value of L3‐SMI for predicting the prognosis and complications of cirrhosis. Results: Age and sex had the greatest effects on the L3‐SMI ( P  < 0.001). The L3‐SMI scores were clearly higher in male patients than in female patients (52.94 ± 8.41 vs. 38.91 ± 5.65 cm 2 /m 2, P  < 0.001) and sharply declined in subjects aged ≥ 60 years. Based on the mean −1.28 × SD among adults aged < 60 years, the L3‐SMI cut‐off value for sarcopenia was 44.77 cm 2 /m 2 in male patients and 32.50 cm 2 /m 2 in female patients. Using these values, 22.5% of the cirrhotic patients (28.7% of male patients and 11.9% of female patients) were diagnosed with sarcopenia. Compared with non‐sarcopenia individuals, sarcopenia patients had lower body mass index (21.28 ± 3.01 vs. 24.09 ± 3.39 kg/m 2, P <  0.001) and serum albumin levels (31.54 ± 5.93 vs. 32.93 ± 5.95 g/L, P  = 0.032), longer prothrombin times (16.39 ± 3.05 vs. 15.71 ± 3.20 s, P  = 0.049), higher total bilirubin concentrations (41.33 ± 57.38 vs. 32.52 ± 31.48 μmol/L, P  = 0.039), worse liver function (Child–Pugh score, 8.05 ± 2.11 vs. 7.32 ± 2.05, P  = 0.001), higher prevalence of cirrhosis‐related complications (81.82% vs. 62.24%, P  < 0.001) and mortality (30.68% vs. 11.22%, P  < 0.001). Overall survival was significantly lower in the sarcopenia group [risk ratio (RR) = 2.643, 95% confidence interval (CI) 1.646–4.244, P  < 0.001], accompanied with an increased cumulative incidence of ascites (RR = 1.827, 95% CI 1.259–2.651, P  = 0.002), spontaneous bacterial peritonitis (RR = 3.331, 95% CI 1.404–7.903, P  = 0.006), hepatic encephalopathy (RR = 1.962, 95% CI 1.070–3.600, P  = 0.029), and upper gastrointestinal varices (RR = 2.138, 95% CI 1.319–3.466, P  = 0.002). Subgroup analysis showed sarcopenia shortened the survival of the patients with Model For End‐Stage Liver Disease score > 14 (RR = 4.310, 95% CI 2.091–8.882, P  < 0.001) or Child–Pugh C (RR = 3.081, 95% CI 1.516–6.260, P  = 0.002). Conclusions: Sarcopenia is a common comorbidity of cirrhosis and can be used to predict cirrhosis‐related complications and the prognosis.